Bmi1 deficient neural stem cells have increased Integrin dependent adhesion to self-secreted matrix - Bruggeman, Sophia W.M.; Hulsman, Danielle; van Lohuizen, Maarten (Biochimica et biophysica acta, 2009)
Neural cells deficient for Polycomb group (PcG) protein Bmi1 are impaired in the formation and differentiation of high grade glioma, an incurable cancer of the brain. It was shown that mechanisms involved in cell adhesion and migration were specifically affected in these tumors. Using biochemical and cell biological approaches, we investigated the adhesive capacities of Bmi1;Ink4a/Arf deficient primary neural stem cells (NSCs). Bmi1;Ink4a/Arf deficient NSCs have altered expression of Collagen-related genes, secrete increased amounts of extracellular matrix, and exhibit enhanced cell–matrix binding through the Beta-1 Integrin receptor. These traits are independent from the well described role of Bmi1 as repressor of the Ink4a/Arf tumor suppressor locus. In addition to proliferative processes, Bmi1 controls the adhesive capacities of primary NSCs by modulating extracellular matrix secretion. Since PcG protein Bmi1 is important for both normal development and tumorigenesis, it is vital to understand the complete network in which this protein acts. Whereas it is clear that control of Ink4a/Arf is a major Bmi1 function, there is evidence that other downstream mechanisms exist. Hence, our novel finding that Bmi1 also governs cell adhesion significantly contributes to our understanding of the PcG proteins.